Day 3 IFPRI Presentations for 2023 CGIAR GENDER-ICAR Conference - Go, Ara; Raghunathan, Kalyani; Paz, Florencia; Ray, Soumyajit; Gupta, Shweta; Lambrecht, Isabel B.; Falk, Thomas; Bartels, Lara; Duche, Vishwambhar; Vollan, Björn (2023)
IFPRI is participating in the 2023 annual CGIAR Gender Research Conference. This conference is co-hosted by the CGIAR GENDER Impact Platform and the Indian Council of Agricultural Research (ICAR) and will take place in New Delhi, India, on October 9-12, 2023.